Presenting the Secrets: Exploring Endogenous Defense Mechanisms in Chrysanthemums against Aphids - Changchen Xia; Wanjie Xue; Zhuozheng Li; Jiaxu Shi; Guofu Yu; Yang Zhang (Horticulturae, 2023)
As the second-largest cut flower plant globally and one of the top ten traditional flowers in China, chrysanthemums hold significant economic value, encompassing both ornamental and medicinal applications. However, aphids pose a considerable threat as one of the most critical pests affecting chrysanthemums. These pests not only diminish the ornamental value of chrysanthemums through feeding and reproduction but also transmit numerous plant viruses, causing irreversible damage. This review examines aphids’ feeding and damage patterns as a starting point, highlighting the unique endogenous defense mechanisms that have evolved in chrysanthemums during their continuous struggle against aphids. These mechanisms include constitutive defense and induced defense. In addition, we enumerate aphid-resistance genes that have been reported in chrysanthemums. Furthermore, this paper compares and predicts the aphid-resistance genes of other species based on the published Chrysanthemum nankingense genome, aiming to provide a valuable reference for future research on aphid-resistance genes in chrysanthemums.